2021
DOI: 10.1109/jbhi.2020.2984647
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Spatio-Temporal Cardiac Action Potential Variability at Baseline and Under $\beta$-Adrenergic Stimulation by Combined Unscented Kalman Filter and Double Greedy Dimension Reduction

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…The currents were: I Ks , I Kr , I to , I CaL , I K1 , I N a , I N aCa and I N aK . From the 8000 models initially generated by a Monte-Carlo method, only 2373 models were retained after a calibration step based on physiological limits of electrical properties, as described in [6]. The calibrated models represent virtual cells with distinct ionic properties.…”
Section: Stochastic Population Of Ap Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The currents were: I Ks , I Kr , I to , I CaL , I K1 , I N a , I N aCa and I N aK . From the 8000 models initially generated by a Monte-Carlo method, only 2373 models were retained after a calibration step based on physiological limits of electrical properties, as described in [6]. The calibrated models represent virtual cells with distinct ionic properties.…”
Section: Stochastic Population Of Ap Modelsmentioning
confidence: 99%
“…DGDR, a methodology for high-dimensional data analysis [3], was first applied to estimate the AP model parameters by projecting the input data into a low subspace through a sparse linear combination of dictionary entries. The dictionary was composed by different AP markers, like AP duration at different percentages of repolarization, short-term variability (STV) of AP duration, peak voltage, resting membrane potential or wavelet decomposition components, among others, as well as linear combinations of these markers [6].…”
Section: Parameter Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying such a QT lag reduction are yet unclear. In silico studies have investigated the dynamics of cellular repolarization duration in response to β -adrenergic stimulation [ 34 , 35 ] and have shown that the time lag of the action potential (AP) duration (APD) in response to β -adrenergic stimulation becomes reduced for higher pre-stimulation levels of β -adrenoceptors [ 36 ]. Based on these studies, we hypothesized that the enhanced sympathetic activity when getting closer to the stress peak, and thus increasingly higher β -adrenergic stimulation, could play a role in the observed QT lag reduction at the end of the exercise.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, computational modeling and simulation has taken a growing role as a method to deepen the understanding of cardiac function in health and disease [1,2]. Novel in silico models of increasing complexity are continuously being developed to simulate the electrophysiology [3] and mechanics of the heart [4] from the cell [5] to the whole-organ level [6]. At the tissue and organ levels, electrophysiology is simulated by using the well-known bidomain [7] and monodomain [8] models.…”
Section: Introductionmentioning
confidence: 99%